In-vitro antioxidant and antimicrobial studies of ethanolic plant extracts of P. granatum, O. stamineus, A. bilimbi, M. nigra, and E. longifolia - Makky, Essam A.; Manaf, Almatar; Mahmood, Mahmood H. (Bentham Science, 2021)
Background: Acne is a serious skin problem that affects mostly adolescents. The topical and systematic therapies are effective but could lead to several side effects and the emergence of antibacterial resistance of the acne-causing bacteria. Plant resources have been used as traditional medicine for centuries and can be the alternative therapies for acne treatment. Antioxidants are compounds that can prevent or delay the oxidation of substrates when present in low concentrations. Antioxidants are usually involved in several mechanisms of action, including the inhibition of free radical generation, enhancement of the scavenging capacity against free radicals, and reducing power. Methods: In this study, three antioxidant assays, DPPH, ABTS, and FRAP were used to evaluate the antioxidant properties of the ethanolic extracts of five plant extracts (A. bilimbi, M. nigra, O. stamineus, P. granatum, and E. longifolia). Furthermore, the study aimed to identify the most potent plant extracts and their combination which could provide better antibacterial activities against acne-causing bacteria. Ethanolic extracts of A. bilimbi, O. stamineus, M. nigra, P. granatum, and E. longifolia were prepared by the Ultrasound-Assisted Extraction (UAE) technique. Their phytochemical contents were screened using several biochemical tests and GC-MS analysis. Results: The study found that only the extracts of P. granatum and O. stamineus exhibited good antioxidant activity using DPPH assay (82.37% and 81.72% μg/mL respectively) and in ABTS assay (87.25% and 88.85% μg/mL respectively); their observed FRAP values were 115.1667 ± 5.6182 and 41.3860 ± 2.4583 μg/mL, respectively. The preliminary antibacterial screening using the disc diffusion method showed that P. granatum and O. stamineus were the most potent extracts; hence, both extracts were combined at the ratios of 1:1, 1:2, and 2:1 to a total concentration of 400 mg/mL. Discussion: The antibacterial efficacy of the mixture was studied using the disc diffusion method and the MIC value was determined. Both S. aureus and S. epidermidis were sensitive to all the individual and combined extracts but C. acnes was resistant to all of them. Conclusion: The antibacterial activity of the combined extracts against S. aureus showed a synergistic effect at the ratio of 2:1 with the inhibitory zone diameter of 18.00 ± 1.00 mm and MIC value of 12.5 mg/mL; however, antagonistic effects were observed against S. epidermidis while no effect was noted against C. acnes. Therefore, all the selected plant extracts exhibited antibacterial activities against certain bacteria and their effects may be enhanced by combining the plant extracts.